Comparison of the financial cycle in advanced and emerging economies - Monteiro, Ornella Lassalette (2016)
This dissertation argues that financial cycles are different for advanced economies and emerging countries. The main underlying reason is the different financial development that makes for instability in emeging markets which is pronounced by more intensive and amplified financial cycle. As such, even the policy implications are different.